Petrogenesis of the peralkaline granite (and associated syenite) dykes of the Straumsvola Complex, Western Dronning Maud Land, Antarctica - Dreyer, Tanya Shayna (Department of Geological Sciences, 2016)
The Straumsvola nepheline syenite complex in Western Dronning Maud Land, Antarctica consists of an outer massive and inner layered nepheline syenite that is itself intruded by ijolite. The complex and its immediate country rock was intruded by numerous dykes. A small proportion of these dykes are peralkaline syenite and microgranite, and these are found only to intrude the nepheline syenite and not the country rock. The presence of peralkaline granite dykes intruding a silica-undersaturated complex is unexpected, given the thermal divide that exists at low pressures between silica-under and -oversaturated phases. Major and trace element variations in the dykes are found to be consistent with fractional crystallisation of a parental peralkaline magma of trachyte composition.